2014
DOI: 10.1016/j.ksujds.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer trends in Iraq from 2000 to 2008

Abstract: Background: The aim of this study was to identify differences in oral cancer incidence among sexes, age groups and oral sites over time in Iraqi population. Methods: Data was obtained from Iraqi cancer registry, differences and trends were assessed with the Wilcoxon matched-pairs signed-ranks test and Regression test, respectively. Results: In Iraq from 2000 to 2008, there were 1787 new cases of oral cancer registered, 1035 in men and 752 in women. Cancer at all oral sites affected men more than women. The Ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
(13 reference statements)
2
19
1
Order By: Relevance
“…The age of the patients ranged from less than 1 year Table 1 Key oral pathology studies in Iraq: this is a summary table of key oral and maxillofacial histopathology studies carried out in Iraq. The majority of studies have focussed on certain pathological entities or groups, rather than reporting the whole range of oral and maxillofacial histopathology 33 Oral cancer 1787 2000-2008 (Iraq) Khudier, 2012 28 Oral malignancy 82 2004-2009 Sulaimania Naji, 2012 20 Salivary gland lesions 66 2005-2010 Babil Yas, 2012 43 Lichen planus 194 1985-2010 Baghdad Murad, 2011 44 Odontogenic keratocysts 52 1990-2000 Baghdad Salih, 2011 45 Pyogenic granuloma 100 2000-2010 Nasiriyya Al-Kawaz, 2010 31 Oral to 90 years of age, with most patients being in their second to fourth decades of life ( Figure 1). Most of the samples were in the mucosal and skin pathology category, making up more than one-third of all the oral and maxillofacial specimens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The age of the patients ranged from less than 1 year Table 1 Key oral pathology studies in Iraq: this is a summary table of key oral and maxillofacial histopathology studies carried out in Iraq. The majority of studies have focussed on certain pathological entities or groups, rather than reporting the whole range of oral and maxillofacial histopathology 33 Oral cancer 1787 2000-2008 (Iraq) Khudier, 2012 28 Oral malignancy 82 2004-2009 Sulaimania Naji, 2012 20 Salivary gland lesions 66 2005-2010 Babil Yas, 2012 43 Lichen planus 194 1985-2010 Baghdad Murad, 2011 44 Odontogenic keratocysts 52 1990-2000 Baghdad Salih, 2011 45 Pyogenic granuloma 100 2000-2010 Nasiriyya Al-Kawaz, 2010 31 Oral to 90 years of age, with most patients being in their second to fourth decades of life ( Figure 1). Most of the samples were in the mucosal and skin pathology category, making up more than one-third of all the oral and maxillofacial specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported 31 new cases in 2005 in Mosul province alone. A third study reported 1787 new cases of oral cancer over a 9‐year period, whereas an additional study from Kurdistan region reported 20 cases over a 3‐year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OC is multifactorial in nature, which could be triggered by range of risk factors including drugs, smoking, exposure to sunlight, viruses such as human papilloma virus, occupational hazard, and diet [4]. The prevalence of OC in Iraq was not sufficiently highlighted, and the only available study from 2000-2008 showed that OC was accounted for 2% of all reported cancers, with no clear identification of risk factors or mortality rate of OC [5].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, several epidemiological studies have reported that the prevalence of OC is increased with aging [6]. The majority of Iraqis with OC, from both genders, were aged 60 and above, and the incidence of OC among males is higher than among females [5,7]. At advance stages of OSCC, the clinical picture probably indicates suspicious malignancy, but misdiagnosis is expected at earlier stages [8].…”
Section: Introductionmentioning
confidence: 99%